MENINGKATKAN MOTIVASI BELAJAR DAN KERJA SAMA PESERTA DIDIK MUATAN MATEMATIKA KELAS IV MELALUI MODEL BALANTING DAN PERMAINAN BADAMPRAK DI SDN TABALONG MATI HSU - Zaki Ridhoni, Akhmad; Jannah, Fathul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In this study, the issue is the students' lack of motivation and cooperation, which results in subpar learning outcomes. Researchers used the Badamprak game and the BALANTING model (Problem Based Learning, Numbered Head Together, and Snowball Throwing) to address this issue. The goal of this research is to enhance students' learning motivation, teamwork, and academic performance. The Classroom Action Research (CAR) approach was used in this study, which was conducted over four sessions during the second semester of the 2024/2025 academic year with the topic of eight fourth-grade pupils from Tabalong Mati HSU Elementary School. The data collected consisted of qualitative data from observations of instructors' and students' actions, as well as their drive and collaboration. To assess learning results, quantitative data were collected using written group and individual tests. The outcomes of the study demonstrated that at the fourth session, pupils' motivation to learn rose from 50% to 100%. The level of student cooperation also rose, going from 38% to 100% during the fourth session. From 38% at meeting I to 100% at meeting IV, the classical completeness of pupils' learning outcomes rose. The use of the Badamprak game and the BALANTING model was shown to be successful in boosting students' drive, teamwork, and academic performance.